The Moths of Constância (Ribatejo, Portugal) - a brief sampling (Insecta: Lepidoptera) - J. Rosete; A. Lameirinhas; M. F. C. Corley (SHILAP)
As a result of field work carried out by the first two authors in the area of Constância, Ribatejo, Portugal, in 2018, 89 species of Lepidoptera are added to the fauna of that province. This extends the known distribution of several species in the Portuguese mainland.